Development and application of a simulator for offshore wind turbine blades installation. (15th October 2018) - Ren, Zhengru; Jiang, Zhiyu; Skjetne, Roger; Gao, Zhen
Abstract: In an offshore environment, offshore wind energy resources are more available and stable, but the investment cost is much higher than that of onshore wind. The installation cost is a crucial factor of the investment. With the increasing number of planned and approved offshore wind farms, offshore wind turbine installation and relevant operations have received tremendous attention. Therefore, expediting the turbine-structure mating operations through a higher level of automation in offshore wind turbine installations may provide important economic benefits. To achieve a higher automation level and reduce the weather waiting time during the installation of offshore wind turbines, a flexible simulation-verification framework with high fidelity is needed. However, state-of-the-art wind turbine numerical analysis code is neither convenient nor open enough for applications concerning the design and verification of control algorithms. MATLAB/Simulink is among the most widely utilized numerical platforms by control engineers and researchers. This paper describes the development of a modularized blade installation simulation toolbox for the purpose of control design in MATLAB/Simulink. The toolbox can be used to simulate several blade installation configurations, both onshore and offshore. The paper presents the key features and equations of the different modules, exemplified by a single blade installation operation. Code-to-code verification results are presented and discussed with both quasi-steady wind and three-dimensional turbulent wind field. Highlights: A modularized numerical modeling framework for wind turbine installation is developed. Code-to-code verification studies are conducted for single blade installation method. The toolbox is also capable of simulating other offshore installation operations.